2020
DOI: 10.1111/1747-0080.12610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary intake and decision‐making during pregnancy on birth outcomes

Abstract: Aim: This study aimed to examine dietary intake and decision-making in a cohort of pregnant South-East Queensland women to determine compliance with dietary guidelines and the relationships between dietary intake, decisionmaking and birth outcomes.Methods: Pregnant women attending maternity services at participating hospitals reported food frequency and motivations using the Maternal Outcomes and Nutrition Tool, a novel digital instrument. Birth outcomes were sourced from hospital records. A cross-sectional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The findings of our study are in line with other research showing that there is poor adherence to pregnancy dietary recommendations, including intakes of vegetables, wholegrains, folic acid, and iron. 15,16 Fruit, vegetables, wholegrains, and fish are key components of the Dietary Approaches to Stop Hypertension (DASH) dietary pattern and following this diet has been associated with lower maternal blood pressure, even in women without hypertensive disorders. 17 The most common dietary issue in our study was self-reported fish intake of less than once a week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of our study are in line with other research showing that there is poor adherence to pregnancy dietary recommendations, including intakes of vegetables, wholegrains, folic acid, and iron. 15,16 Fruit, vegetables, wholegrains, and fish are key components of the Dietary Approaches to Stop Hypertension (DASH) dietary pattern and following this diet has been associated with lower maternal blood pressure, even in women without hypertensive disorders. 17 The most common dietary issue in our study was self-reported fish intake of less than once a week.…”
Section: Discussionmentioning
confidence: 99%
“…20 Low consumption of vegetables is associated with hypertensive disorders in pregnancy. 16 Inadequate knowledge of dietary recommendations is one potential barrier for pregnant women to adhere to nutrition guidelines during pregnancy. 21 Percentage of pregnant women agreeing with each statement about the conversaƟon with the healthcare professional using the FIGO NutriƟon Checklist F I G U R E 5 Attitudes of pregnant women and healthcare professionals to the FIGO Nutrition Checklist.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy dietary intake during pregnancy is important for maternal and child health (World Health Organization, 2018) which has been defined by the World Health Organization (2018) as one that "contains adequate energy, protein, vitamins and minerals, obtained through the consumption of a variety of foods, including green and orange vegetables, meat, fish, beans, nuts, pasteurized dairy products and fruit (p. 4)". A poor dietary intake is associated with adverse health outcomes for the mother (e.g., increased risk of pre-eclampsia and gestational diabetes, and excessive gestational weight gain), adverse birth outcomes (e.g., premature birth and low birth weight), and adverse health outcomes in childhood and adult life (e.g., increased risk of developing chronic diseases such as diabetes or coronary heart disease) (James-McAlpine et al, 2020;Ramakrishnan et al, 2012;Stang & Huffman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several papers in this issue provide further evidence of the importance of adequate and timely nutrition in the first 1000 days and the need for this to be communicated effectively to new mothers and mothers to be. While pregnancy is seen as a critical window of opportunity for promoting healthy eating to women, food choices of pregnant women appear to be driven primarily by sensory and not health motives, 22 as is the case in the general population. In particular, the iodine intake of pregnant women continues to be of concern, with dietary intakes likely to be insufficient, and the importance of iodine in pregnancy is seemingly ineffectively communicated to this target group.…”
mentioning
confidence: 91%
“…Sherriff et al investigated the dietary iodine intake of pregnant women attending antenatal classes in Perth and found that only three of five women consumed bread daily 8 . Similarly, James‐McAlpine et al assessed the diets of a cohort of pregnant South East Queensland women and found that the daily serves of grain‐based food were less than half the recommended intake 22 . The implication of both these studies is that the dietary intake of both folate and iodine by pregnant Australian women is likely to be insufficient…”
mentioning
confidence: 99%